If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 = 5t + 4 Reorder the terms: -6 = 4 + 5t Solving -6 = 4 + 5t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5t' to each side of the equation. -6 + -5t = 4 + 5t + -5t Combine like terms: 5t + -5t = 0 -6 + -5t = 4 + 0 -6 + -5t = 4 Add '6' to each side of the equation. -6 + 6 + -5t = 4 + 6 Combine like terms: -6 + 6 = 0 0 + -5t = 4 + 6 -5t = 4 + 6 Combine like terms: 4 + 6 = 10 -5t = 10 Divide each side by '-5'. t = -2 Simplifying t = -2
| p/7=21 | | 6x+4=20x+7 | | 11x-8=12+x | | -16m=48 | | 2p^2+3p^2-8p^3-6p^3= | | 6x+4-1=20x+6 | | 3x-2(7-2y)=10 | | 4x-3=2x-5 | | -13+6x-7+3x=1+x | | 6x+4-1=20x+1 | | 2p^3+3p^2-8p^3-6p^3= | | y/(-8)=9 | | 2x+7=-7x+88 | | 31=-16m | | 5(5.5)+7=9(5.5)-15 | | 28=4(x-5) | | 0=x^2+6x-11 | | 24x-8-10x=-2(4-7x) | | -299=-23m | | 512x^9-729x^15= | | 21.8=.7x | | 5m+6=-21 | | -3-3(t-2)= | | 24x-8-10x=-2(4-7) | | 8x+4=3(2x+1)-x+6 | | x+1x+15= | | -3x^3+24= | | -x+8+5x=6x+16 | | 120(22+y)=98(6+y) | | -3-(2-4p)= | | 4+t/5=-8 | | (11*7)+(15)= |